GESTATIONAL DIABETES MELLITUS: APPROACH TO THE MAIN CHANGES IN THE MATERNAL BODY, WITH A FOCUS ON DERMATOLOGICAL MANIFESTATIONS (Editora Impacto Científico, 2025)
Diabetes Mellitus (DM) is a chronic disease with high global prevalence, associated with severe microvascular complications, among which Diabetic Retinopathy (DR) stands out. This condition affects approximately one-third of individuals with DM and is one of the leading causes of preventable blindness worldwide. The present study conducted a literature review on the relationship between DM and DR, analyzing articles published between 2014 and 2024 in the PubMed, SciELO, LILACS, and MedLine databases. The results indicate that persistent hyperglycemia is the main etiological factor for DR, whose progression is directly related to inadequate glycemic control. Clinical manifestations range from non-proliferative to proliferative forms, potentially progressing to macular edema and blindness. Early diagnosis through ophthalmological exams and retinography, combined with appropriate management including laser photocoagulation and strict metabolic control, is essential to prevent severe complications. It is concluded that systematic screening and continuous follow-up are indispensable strategies to reduce morbidity and preserve the quality of life of diabetic patients.DOI: https://doi.org/10.56238/edimpacto2025.091-005